Application of The Problem Solving Learning Model Assisted by Roulette Media in Student History Subjects in Aceh Besar District - Nurvazillah Nurvazillah; Muhjam Kamza (Universitas Syiah Kuala, 2022)
This study aims to find out how the application and response of class XI IPS 1 students in the application of problem solving learning models assisted by roulette media in history learning at SMA Negeri 1 Kuta Cot Glie, Aceh Besar District. This research uses a qualitative approach with descriptive research type and the sampling purposive sampling. The subjects in this study were students of class XI IPS 1, totaling 24 students. Based on the results of the research, it is known that (1) The application of the problem solving learning model assisted by roulette media in history learning in class XI IPS 1 has been carried out well according to the problem solving syntax. This can be seen from the results of the analysis of the application of the learning model, an average score of 78,3% is included in the good criteria and the results of the learning mastery analysis show that 21 people scored above the minimum criteria of mastery learning or equivalent to 87,5%, while 3 people scored below the minimum criteria of mastery learning or equivalent to 12,5%. (2) The response of class XI IPS 1 students in the application of learning with problem solving models assisted by roulette media is good. This can be seen from the activities and behavior of students shown in learning activities, students listen and follow the teacher’s directions in accordance with the learning syntax. Students solve the problems given by the teacher carefully and keep the class organized.